THREE ESSAYS ON POLITICAL ECONOMY OF OIL REVENUES IN THE AFRICAN STATES - (:unkn) unknown (My University, 2010)
The vision of the role of natural resources in the development process has changed over the last thirty years. The optimistic views of the beginning became more moderate, even pessimistic. This thesis focuses on the role of oil in the political, institutional, and economic performances of African countries, some of which are richly endowed. It revolves around three empirical essays. Chapter 2 focuses on the duration of political regimes in Africa and shows from a duration model that revenues from oil exploitation play an important role. Chapter 3 examines the high indebtedness of oil-producing countries. A collateral effect of oil resources is highlighted, it dominates an instability effect. Chapter 4 includes, in a dynamic computable general equilibrium model, the permanent income hypothesis presented in the literature as the answer to the fiscal management of oil revenues. It concludes that a relevant rule of oil revenues management in African countries should not reduce only the impact of volatility on public finances, but it should also address the development needs of African oilproducing countries.
Keywords: African Research